2008
DOI: 10.1002/jrs.2021
|View full text |Cite
|
Sign up to set email alerts
|

Raman spectroscopy of synthetic organic pigments used in 20th century works of art

Abstract: Raman microscopy allows a non-destructive characterisation of inorganic and organic painting materials such as pigments and organic dyestuffs. The objectives of this study are the more recent organic pigments typically present in paintings and other art works from the 20th century. More than 20 organic synthetic pigments from different chemical classes could be identified by Raman spectroscopy using different excitation wavelengths (457.9, 476.5, 487.9, 514.5, 632.8, and 1064 nm). To evaluate the performance f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
60
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(65 citation statements)
references
References 19 publications
3
60
1
Order By: Relevance
“…[56 -58] The prominent bands at 1175 (C-N symmetric stretch), 1397 (N N stretch), 1478 (azobenzene ring vibration) and 1615 cm −1 (benzene ring stretching) are indicative of a modern synthetic azo dye or pigment (the organic purple dye/pigment has the following bands: 238w, 436s, 531w, 664w, 797m, 917w, 1175s, 1215w, 1308m, 1363s, 1397s, 1478s, 1542s, 1615s cm −1 ). [57,59] This compound was used mainly in mixtures, especially in green areas together with lead chromate. It was found specifically in most foliage and grass areas, as well as on clothing and architectural details.…”
Section: Blacksmentioning
confidence: 99%
“…[56 -58] The prominent bands at 1175 (C-N symmetric stretch), 1397 (N N stretch), 1478 (azobenzene ring vibration) and 1615 cm −1 (benzene ring stretching) are indicative of a modern synthetic azo dye or pigment (the organic purple dye/pigment has the following bands: 238w, 436s, 531w, 664w, 797m, 917w, 1175s, 1215w, 1308m, 1363s, 1397s, 1478s, 1542s, 1615s cm −1 ). [57,59] This compound was used mainly in mixtures, especially in green areas together with lead chromate. It was found specifically in most foliage and grass areas, as well as on clothing and architectural details.…”
Section: Blacksmentioning
confidence: 99%
“…Recent organic painting materials such as pigments typically present in paintings and other art of works from the 20th century are the materials of interest in a study by Schulte et al [64] The authors identified more than 20 organic synthetic pigments from different chemical classes. Another pigment analysis, however, from art works of the 16th to 18th century was performed by Burgio et al [65] These authors studied the non-figurative illumination in five Islamic religious manuscripts held in the National Art Library at the Victoria and Albert Museum, London, UK, and concluded that the range of pigments was stable during the 16th and 17th centuries and began to expand in the 18th century through the introduction of synthetic pigments.…”
Section: Pigments Dyes Paints and Inksmentioning
confidence: 99%
“…Inorganic pigments are increasingly being displaced by synthetic organic pigments and they are now the most important group of pigments in the bright hues of modern artist's paints (Scherrer 2009). The interest in the properties of synthetic organic pigments has increased significantly in recent years, both in the historical (de Keijzer 1988(de Keijzer , 1989(de Keijzer , 1999(de Keijzer , 2002Frowein 2004;Fritsch 2006) and technological context (Lomax 2006;Lutzenberger 2009;Strauss 1984), as well as in relation to the specific requirements of the material analysis (Strauss 1984;Vandenabeele 2000;Kalsbeek 2005;Schäning 2005;Fritsch 2006;Lomax 2006;Ropret 2008;Schulte 2008;Frowein 2004;Scherrer 2009;Fremout 2012). As versatile as the applications of these pigments are, there also are many associated risks.…”
Section: Introductionmentioning
confidence: 98%